(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2005)
In the context of updating biostratigraphic analysis in the Upper Kimmeridgian-lowermost Berriasian from the whole of the Tunisian Dorsale (NE Tunisia), new results obtained from the Jebel Oust reference section are presented. The bed-by-bed-sampling of a rather rich ammonite fauna gathered in the two most favourable profiles in the area allowed to propose, for the first time, a biozonation for Upper Kimmeridgian to Tithonian limestones. Calpionellids relayed or completed ammonite assemblages, and were also useful for biostratigraphy in beds close to the Jurassic-Cretaceous boundary. The composition of ammonite assemblages, as well as the known ranges for genera and species, is in accordance with the available information from epioceanic areas in West-Mediterranean Tethys. The recognized biozones fit the standard proposal given by Groupe Français D’Etude du Jurassique in 1997. Age-interpretation for turbiditic horizons in the Jebel Oust is made for the first time. In spite of some limitations, the biostratigraphic results obtained in Jebel Oust sections provide a valuable tool for potential correlations with poorly known sections in northern Tunisia, as well as with other Tethyan areas.